Intelligenza artificiale, conoscenze neuroscientifiche e decisioni giuridiche - Santosuosso, Amedeo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2021)
The paper addresses some topics at the intersection of neuroscience, artificial intelligence (AI) and law. The problem of AI is not only the development of more powerful machines, but the cognitive architecture of the intelligence model that is assumed as a reference. But until we better understand how human cognition works, we will not even make decisive steps on ‘general’ artificial intelligence. Law is a rich test case and an important field for the development of logic-based artificial intelligence, particularly with regard to logical models of legal argumentation. The question of the relationship between law and logic (and which logic) and between law and AI intertwines with legal traditions (mainly rationalist or historicist ones) and with the orientations present in the IA debate, and gives rise to complex and open questions. In particular, the relationship between logicist (or rationalist) and non-logicist (or historical) orientations in AI and law is considered.